The restoration potential of fynbos riparian seed banks following alien clearing - Vosse, Shelly (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScConsEcol(Conservation Ecology and Entomology)--University of Stellenbosch, 2007.